A new species of Ptychognathus Stimpson, 1858 (Crustacea: Decapoda: Brachyura: Varunidae) from the Ryukyu Islands, southwestern Japan - Osawa, Masayuki; Ng, Ngankee (Zootaxa, 2006)
A new varunid crab, Ptychognathus insolitus, is described from Izena Island, the Ryukyu Islands, southwestern Japan. This new species is unique among congeners in having a very broad carapace, long and slender ambulatory legs, and stout male first gonopods. Although these characters are diagnostic to Orcovita Ng & Tomascik, 1994, the new species belongs to Ptychognathus Stimpson, 1858 based on the lack of a distinct frontal median triangle on the carapace and the short dactyli of the fifth pereopods.